Mobile application for advertising faculty educational services - Galyna V. Marchuk; Vitalii V. Levkivskyi; Maryna S. Graf; Yelyzaveta A. Dombrovska; Iryna V. Panarina (Educational Technology Quarterly, 2023)
The article shows the use of augmented reality technology and the creation of a mobile application for advertising educational services of the Faculty of Information and Computer Technologies of the Zhytomyr Polytechnic State University, Ukraine. The research method is the use of augmented reality technology to create mobile applications using the Vuforia platform. The developed application is intended for use on devices running on the Android operating system. As a result of this work, a mobile software application was designed and created to promote educational services of the Faculty. Animated 3D models created using the Blender package, cards with information on each specialty and animated videos were created. There is a possibility of direct transition from the mobile application to external information resources. The proposed development can be used to promote the educational opportunities of the educational institution, increase the information value of advertising paper advertising and greater interest of entrants. Mobile application prototype tested in production environment and can be used by multiple faculties. For use by other faculties, information about the relevant specialties must be added to the program. As a result of using the developed mobile application, the number of applications from entrants to the faculty has increased by 40 percent over the past three years.